Organizational Justice, Behavioral Ethics, and Corporate Social Responsibility: Finally the Three Shall Merge. (2nd April 2015) - Rupp, Deborah E.; Wright, Patrick M.; Aryee, Samuel; Luo, Yadong
<x content-type="archive" xml:space="preserve">Abstract</x> Issues of ethics, justice, and social responsibility are as fundamental to organizational behavior as they are to society at large. As contracts are forged, individuals employed, and power differentials created, opportunities for exploitation, oppression, and victimization emerge. In contrast, as social structures evolve, coordinated opportunities arise for imparting positive social change at the community, environmental, and societal levels. Inherent to all of these phenomena is the application of norms surrounding moral behavior. Norms about what is considered fair and ethical underlie how individuals perceive and evaluate the behaviors and decisions of others; how groups and societies define acceptable behavior; and how individuals, groups, and societies evaluate the decisions and actions of organizations. In addition to defining standards, these norms also drive the reactions (or sanctions) against those who violate them.